2023
DOI: 10.1039/d3nr02995f
|View full text |Cite
|
Sign up to set email alerts
|

Tunable non-volatile memories based on 2D InSe/h-BN/GaSe heterostructures towards potential multifunctionality

Abstract: The floating gate memory based on two-dimensional van der Waals (2D vdWs) heterostructures plays an important role in the development of the next generation information technology. The diversity of 2D...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…This memory exhibited ultrahigh-speed operation of 21 ns. Coincidentally, Gong et al 219 reported tunable non-volatile memories based on 2D InSe/h-BN/GaSe heterostructures. InSe, h-BN and GaSe serve as the active channel, insulating layer and floating gate layer.…”
Section: Inse Advanced Device Applicationmentioning
confidence: 99%
“…This memory exhibited ultrahigh-speed operation of 21 ns. Coincidentally, Gong et al 219 reported tunable non-volatile memories based on 2D InSe/h-BN/GaSe heterostructures. InSe, h-BN and GaSe serve as the active channel, insulating layer and floating gate layer.…”
Section: Inse Advanced Device Applicationmentioning
confidence: 99%